Preliminary analysis of gut microbiome characteristics in children with obstructive sleep apnea hypopnea syndrome - Wang, Zhihui; Zhou, Luting; He, Yanyu; Xv, Xueyun; Lv, Meng; Zhang, Zhen; Wang, Fengqian; Wang, Shuqi; Wang, Yuqing (Frontiers in Neurology, 2025)
ObjectiveTo analyze the characteristic changes in the gut microbiome in children with obstructive sleep apnea-hypopnea syndrome (OSAHS) and to investigate the relationship between the gut microbiome and polysomnography (PSG) results.MethodsChildren diagnosed with primary snoring and OSAHS by PSG were enrolled in the study group. Nonsnoring children undergoing elective surgery were selected as the control group. Stool, sleep monitoring data, and medical history data were collected. The clinical history data were analyzed by SPSS 25.0 software. 16S rRNA high-throughput sequencing technology was used to analyze the gut microbiome, and relevant biostatistical methods were used to analyze and describe the characteristics of the gut microbiome.ResultsA total of 62 OSAHS patients (42 mild OSAHS and 20 moderate to severe OSAHS), 16 primary snoring patients and 46 controls were enrolled in this study. There were significant differences in the partial alpha diversity index (observed otus index, Chao1 index) and beta diversity under the Jaccard and unweighted UniFrac distance methods between the mild OSAHS group and the moderate to severe OSAHS group. There were differences in some gut microbiome at different levels of phylum, class, order, family, genus and species between the control group and OSAHS group. There was a significant difference in the abundance ratio between Firmicutes and Bacteroidetes (F/B), and the ratio gradually increased among the three groups. The predictive model for OSAHS diagnosis established by the receiver operating characteristic (ROC) curve showed that the area under the curve (AUC) of Firmicutes and the F/B were more than 50%. At the genus level, Akkermansia was positively correlated with sleep efficiency (SE), Dialister was positively correlated with mean oxygen saturation (SaO2mean) and lowest oxygen saturation (LSaO2), Escherichia-Shigella was negatively correlated with total sleep time (TST), and Faecalibacterium was negatively correlated with the obstructive apnea index (OAI).ConclusionThe gut microbiome of children with OSAHS is slightly different at the phylum, class, order, family, genus and species levels. The F/B and Firmicutes abundance detection have limited predictive capability for the diagnosis of OSAHS. At the genus level, some gut microbiota were correlated with PSG indicators.